Public theology for peace photography: a critical analysis of the roles of photojournalism in peacebuilding, with the special reference to the Gwangju Uprising in South Korea - Kim, Sangduck (The University of Edinburgh, 2018)
In this thesis, I investigate the different ways in which photography can be used to build peace in conflict situations. Although its role can be ambivalent, I primarily focus on its positive uses with the question: to what extent can photography promote peace rather than violence and conflict? My contention is that photography has the potential to contribute to building peace through several important roles in pre-conflict, post-conflict, and conflict situations: it can bear witness to truth, represent victims’ suffering, encourage nonviolent resistance against violence, reconstruct painful memories, and re-imagine justice and reconciliation. To do this, I primarily focus on the May 18th Gwangju Democratic Uprising which happened between the 18th and 27th of May 1980 in the city of Gwangju, in the south-western region of South Korea. In the first chapter, I explore the relation between photography and peacebuilding, providing a brief history of “war photography” particularly between the mid-19th century and the mid-20th century. I focus on two movements in war photography—realism and surrealism. Then, I consider the role of war photography from a peacebuilding perspective, by focusing on the concept of “social psychological distance” between photographs and audience. In the second chapter, I consider how a photograph can reveal truth in violent conflict situations, focusing on the concept of “bearing witness”. In comparison with the concept of “eye witnessing”, I examine how photographs have contributed to bearing witness to violent events. In this fashion, I focus on the importance of journalists and their roles as bearing witness to truth. In the third chapter, I investigate how photography can represent a victim’s suffering and promote empathy. For this, I re-examine compassion fatigue theory, drawing upon the work of Susan Sontag and Susan Moeller. I then explore the theme through analysis of social documentary photography in the mid-twentieth century in the United States. In the fourth chapter, I argue that photography has the potential play an active role in empowering people to overcome fear and resist violence nonviolently. This offers a balance to those who propose a compassion fatigue theory, arguing that repeated exposure to violent images can reduce moral sensibility. In other words, even though photography can produce cultural fatigue from overwhelming violent representations, it can also promote moral sensibility and social actions against violence. In the fifth chapter, I investigate the role of photography in the aftermath of violent conflict, mainly focusing on the relationship between remembering and painful history. Drawing on cultural memory theories such as those developed by Maurice Halbwachs and Aleida and Jan Assmann, I contend that social identities can be reconstructed through the process of remembering. I argue that photography can be a tool for remembering the painful history wisely, mainly focusing on reconstruction of identity and healing of cultural trauma (Hicks 2002; Volf 2006). I explore how photography contributes to the practice of remembering painful history rightly. In the final chapter, I focus on reconciliation and restorative justice as an alternative approach to building a just and peaceful society in the aftermath of a conflict such as the Gwangju Uprising. Because of the relational aspect of reconciliation and restorative justice, I argue, the approach can contribute to the development of the ‘moral imagination’ that overcomes the limits of the current juridical justice system. Reconciliation cannot be only the end of peacebuilding, but also a practical guideline for achieving both peace and justice.
Keywords: public theology; peacebuilding; photography and photojournalism; Gwangju Uprising; May 18 Democratic Uprising; peace and reconciliation; media studies